Human Resource Information Systems (HRIS) In Modern Business (International Journal of Scientific Research and Management (IJSRM), 2014)
: Organizations have started to use information systems in various functions and departments in the last decades with the advent of globalization and liberalization. The department of Human Resources are highly used Management Information System (MIS) for their effective functioning. Human Resource Information System supports Identifying potential employees, Maintaining complete records on existing employees, Creating programs to develop employees ‘talents’ and skills. Human Resource Information Systems helps top level management to identify the manpower requirements to meet the organization’s long term business plans and strategic goals. Human Resource Information Systems also helps the middle level management to monitor the recruitment and allocation of works and compensation to employees. Human Resource Information Systems extend helps to operational management to place the employees. In this research paper, effectiveness of Human Resource Information System in organization is clearly dealt with and offer valuable suggestions to initiate vibrant Human Resource Information System.